Intensitas Serangan Xanthomonas oryzae pv. oryzae pada Beberapa Varietas Padi Sawah dan Dampaknya terhadap Pertumbuhan dan Hasil Panen: bahasa inggris - pinem, Terkelim; syarif, zulfadly (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2018)
The attack intensity of several rice varieties to bacterial leaf blight (BLB) disease caused by Xanthomonas oryzae pv. oryzae is assumed to be different. This study aimed to determine the intensity of BLB attacks on several rice varieties and determine level of resistance. The research was conducted from April to July 2016 on experimental land of Center for Agricultural Training (BBPP) of Batangkaluku, Gowa Regency, South Sulawesi Province. The study used an experimental method with Randomized Block Design (RBD) in 6 treatments and 4 replications. The treatment in the form of 6 rice varieties, namely: IR 64, Ciherang, Situ Bagendit, Sintanur, Mekongga, and Celebes. The results showed that all varieties were included in the criteria of moderately resistant to bacterial leaf blight X. oryzae pv. oryzae. The attacks of BLB tended to increase every week, with the highest attacks found on 84 day after planting. The highest attack was found at 84 day after planting. The most resistant variety was Mekongga with the intensity of attacks ranging from 0 – 7.09% (resistant - moderately resistant) and able to provide the highest yield of 7.2 tons ha-1. Plant height and number of tillers were not affected by bacterial leaf blight attacks.